Dengue vaccine acceptance and willingness to pay - Harapan Harapan; Jonny K. Fajar; R. Tedjo Sasmono; Ulrich Kuch (Taylor & Francis Group, 2017)
The introduction of new vaccines is accompanied by a variety of challenges. Among these, very important ones concern the questions whether the public is willing to accept and willing to purchase the vaccine. Here we discuss factors associated with these questions in the context of vaccines that are becoming available against dengue virus infection. We reviewed published studies available from PubMed and Embase, conducting a meta-analysis when possible and narrative review when the data did not qualify for meta-analysis. We found that attitude toward vaccination and socioeconomic level had significant associations with dengue vaccine acceptance. In addition, socioeconomic level, knowledge, attitude and practice regarding dengue fever, having personally experienced dengue fever and vaccine price were associated with willingness to pay for dengue vaccine. To improve acceptance and willingness to pay for dengue vaccine, well-designed introduction programs that address the associated factors in a context-specific manner are essential.